Conserved regulation of hoxc11 by pitx1 in Anolis lizards. Issue 3 (23rd December 2013) - Park, Sungdae; Infante, Carlos R.; Rivera‐Davila, Laura C.; Menke, Douglas B.
ABSTRACT Anolis lizards are an emerging model system for the study of limb development and evolution, but very little is known concerning the regulatory interactions that control limb patterning differences among Anolis species or what regulatory interactions are deeply conserved between Anolis and other tetrapod groups. Here we report the establishment of an embryonic limb micromass culture system that enables functional studies of forelimb and hindlimb gene regulatory networks in Anolis. Characterization of this culture system demonstrated that embryonic forelimb and hindlimb micromasses from different Anolis species are easy to sustain in culture for weeks, and the expression of forelimb and hindlimb‐specific gene expression patterns are maintained for at least 8 days in culture. We tested the ability of this system to explore regulatory linkages between transcription factors and their putative target genes through the ectopic expression of a hindlimb‐specific transcription factor, pitx1, in forelimb micromasses. We found that pitx1 expression in forelimb cells is sufficient to strongly induce the expression of hoxc11, a gene that normally exhibits hindlimb‐restricted expression. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 156–165, 2014. © 2013 Wiley Periodicals, Inc.